Pengaruh Kualitas Produk, Persepsi Harga, Citra Merek dan Life Style terhadap Keputusan Pembelian: Studi pada Konsumen Pengguna Produk Eiger di Kota Semarang - Fariza Shegi Pratama; Ali Maskur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to find out how factors such as brand image, price perception, product quality, and lifestyle influence purchasing decisions. The research subjects were customers of the Eiger Adventure series products located in Semarang. The quantitative nature of this research refers to primary data collected through Google Form sharing and a sample of 111 respondents selected through a purposive sampling technique. Validity and reliability tests are part of testing the instrument data used. Model testing methods covered in SPSS version 23 include the F test, coefficient of determination (R2), multiple regression analysis, and t test. Based on the research results, it can be said that lifestyle, brand image, price perception and product quality play a role.